Dominant agent and intertemporal emissions trading - Cathrine Hagem; Hege Westskog (University of Oslo, Department of Economics, 2005)
In this paper we analyze how restricting intertemporal trading by prohibiting borrowing of emission permits affects the ability of a dominant agent to exploit its market power, and the consequences this has for the cost-effectiveness of implementing an emissions target. We show that the monopolist could take advantage of the constraint on borrowing by distributing the sale of permits ineffectively across periods, and moreover that this inefficiency is influenced by the way permits are initially allocated between agents. A cost-effective distribution of abatement across periods can be achieved by an appropriate distribution of the total endowments of permits over time for each agent.
Keywords: D92; H74; Q52; 330; pollution permits; intertemporal trading; market power; borrowing constraint; Emissionsrechte; Marktmacht; Intertemporale Allokation; Emissionshandel